(untitled) (Homoeopathy for All, 2024)
Onychomycosis traditionally referred to a non dermatophytic infection of the nail but is now used as a general term to denote any fungal nail infection (Tinea unguium specifically describes a dermatophytic invasion of the nail plate)., Onychomycosis is the most prevalent nail disorder, affecting more than 50% of all nail diseases, and is characterized by fungal infections caused by dermatophytes, yeasts, and non-dermatophyte fungi. This condition typically manifests as discoloration, thickening, and separation of the nail from the nail bed, leading to both aesthetic concerns and potential discomfort.